Lack of bidirectional association between C-reactive protein and depressive symptoms in middle-aged and older adults: Results from a nationally representative prospective cohort study - Li, Xiaohui; Nie, You; Chang, Biru (Frontiers in Psychology, 2023)
Depression is associated with low quality of life and increased health burdens for middle-aged and older adults in resource-limited settings. Although inflammation plays an etiological role in the development and progression of depression, the directionality of the inflammation-depression relationship is unclear, especially in non-Western populations. To examine this relationship among community-dwelling Chinese middle-aged and older adults, we obtained data from the 2011, 2013, and 2015 China Health and Retirement Longitudinal Study (CHARLS). The participants were aged 45 years or above at baseline in 2011 and completed the follow-up survey in 2013 and 2015. Depressive symptoms were measured using the 10-item Center for Epidemiologic Studies Depression Scale (CESD-10), and the C-reactive protein (CRP) level was used to measure individual inflammation levels. Cross-lagged regression analyses examined the inflammation-depression relationship. Cross-group analyses were performed to test for model invariance across the sexes. Pearson’s correlations revealed no concurrent correlations between depression and CRP for both 2011 and 2015 (ps > 0.05, ranging 0.07–0.36) studies. Cross-lagged regression path analyses revealed that the paths from baseline CRP to depression in 2013 (ßstd = −0.01, p = 0.80), from baseline CRP to depression in 2015 (ßstd = 0.02, p = 0.47), from baseline depression to CRP in 2015 (ßstd = −0.02, p = 0.40), and from depression at 2013 to CRP in 2015 (ßstd = 0.03, p = 0.31) were not statistically significant. Additionally, the autoregressive model did not vary across the sexes (△χ2 = 78.75, df = 54, p = 0.02, △ comparative fit index (CFI) <0.01). We failed to find a bidirectional association between the CRP levels and depressive symptoms in our sample.